Experimental Study of TETRA Radio for Railway Communication with Leaky Feeder Configuration - Nattapan Suwansukho; Aditep Chaisang; Thanadol Tiengthong; Sathaporn Promwong (My University, 2023)
In railway voice communication, the digital radio communication, that are widely used whether along the trackside and in the tunnels especially in urban area. The TETRA standard was selected to be used for fulfill the railway operations requirement. Almost TETRA radio system, the configuration almost carried out with the leaky cable configuration This paper presents the experimental study of TETRA radio system with leaky cable configuration, that being used in the railway communication. The frequency being used are between 385–400 MHz. The result shows the calculated received power compared to the actual received signal with the position of train antenna that closed to the leaky cable, the distance is approx. 3 meters.
Keywords: Millimeter-Wave Propagation and Modeling; Power Line Communications and Noise; Advanced MIMO Systems Optimization